Mefloquine reduces the bacterial membrane fluidity of Acinetobacter baumannii and distorts the bacterial membrane when combined with polymyxin B - Nagendran Tharmalingam; Harikrishna Sekar Jayanthan; Jenna Port; Fernanda Cristina Possamai Rossatto; Eleftherios Mylonakis (mBio)
ABSTRACT Acinetobacter baumannii is a high-priority organism for the development of new antibacterial treatments. We found that the antimalarial medication mefloquine (MFQ) permeabilized the bacterial cell membrane of A. baumannii, decreased membrane fluidity, and caused physical injury to the membrane. MFQ also maintained activity across different pH conditions (pH range: 5–8). Structure-activity relationship analysis using MFQ analogs demonstrated that piperidin-2-yl methanol is required for antibacterial activity. Scanning and transmission electron microscopy demonstrated the compromised morphological and membrane integrity in MFQ-treated cells. MFQ synergized with the membrane permeabilizers polymyxin B and colistin and the MFQ + polymyxin B combination killed bacterial cells more effectively than either treatment alone. MFQ + polymyxin B was effective against other gram-negative bacteria including Escherichia coli, Burkholderia pseudomallei, Klebsiella pneumoniae, and Pseudomonas aeruginosa. Bodipy-cadaverine displacement assays confirmed the active interaction of MFQ with other membrane lipid components, such as lipopolysaccharide, lipid A, lipoteichoic acids, and fatty acids. In all-atom molecular dynamics simulations, lipid interactions facilitated the permeation of MFQ into the simulated Gram-negative membrane. Additionally, positively charged nitrogen in the piperidine group of MFQ seems to enhance interactions with the negatively charged components of the bacterial membrane. MFQ + polymyxin B caused significantly greater curvature in the simulated membrane, indicating greater damage than standalone drug treatment. Finally, in vivo assays showed that MFQ + polymyxin B rescued Galleria mellonella larvae infected with A. baumannii. In conclusion, membrane-active agents such as MFQ may warrant further investigation as a potential components of gram-negative infection treatment, particularly in combination with polymyxin B.IMPORTANCEAntimicrobial resistance is a threat globally, and new treatments are urgently needed to combat the rise of multidrug-resistant bacteria. However, the development of anti-infectives has declined over the last two decades due to regulatory, financial and long-term requirement related challenges. In this study, we examined the membrane interactions of the antiparasitic agent mefloquine (MFQ) in combination with polymyxin B, using both in vitro and in silico approaches to evaluate their potential efficacy against gram-negative bacterial infections. We investigated the interaction of MFQ with lipid bilayers to understand the mechanism through which antibacterial activity is exerted. The piperidine moiety of MFQ plays a critical role in its interaction with the lipid bilayer and facilitates membrane permeabilization. In contrast, the membrane permeabilizer polymyxin B is associated with significant neurotoxicity and nephrotoxicity. Our findings highlight the potential of membrane-acting compounds, such as MFQ, to enhance combinatorial activity while mitigating polymyxin B-associated toxicity.